A stretchable, self-healing conductive hydrogels based on nanocellulose supported graphene towards wearable monitoring of human motion. (15th December 2020) - Zheng, Chunxiao; Lu, Kaiyue; Lu, Ya; Zhu, Sailing; Yue, Yiying; Xu, Xinwu; Mei, Changtong; Xiao, Huining; Wu, Qinglin; Han, Jingquan
Graphical abstract: Highlights: A stretchable hydrogel is prepared by dispersing TOCNF-carried GN into PAA. Mechanical toughness and electro-conductibility are enhanced by TOCNF-GN nanocomposites. Hydrogel-based sensor shows high sensitivity and self-healing efficiency. Abstract: Stretchable, self-healing and conductive hydrogels have attracted much attention for wearable strain sensors, which are highly required in health monitoring, human-machine interaction and robotics. However, the integration of high stretchability, self-healing capacity and enhanced mechanical performance into one single conductive hydrogel is still challenging. In this work, a type of stretchable, self-healing and conductive composite hydrogels are fabricated by uniformly dispersing TEMPO-oxidized cellulose nanofibers (TOCNFs)-graphene (GN) nanocomposites into polyacrylic acid (PAA) hydrogel through an in-situ free radical polymerization. The resulting hydrogels demonstrate a stretchability (∼850 %), viscoelasticity (storage modulus of 32 kPa), mechanical strength (compression strength of 2.54 MPa, tensile strength of 0.32 MPa), electrical conductivity (∼ 2.5 S m −1 ) and healing efficiency of 96.7 % within 12 h. The hydrogel-based strain sensor shows a high sensitivity with a gauge factor of 5.8, showing great potential in the field of self-healing wearable electronics.